Kinerja Karyawan Perusahaan Daerah Air Minum (PDAM) Kota Parepare - Arifuddin Arifuddin (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2022)
This study aims to determine the effect of work environment and work discipline partially and simultaneously on employee performance at PDAM Kota Parepare. The analytical method used in this study is a multiple linear analysis methods with the help of SPSS software version 20. The sample in this study were employees in the field of engineering and operations at PDAM Parepare City, totaling 52 employees. The results showed that the work environment had a positive and significant effect on the performance of the employees of the local drinking water company in the City of Pare-Pare by 3,340 > 2,010, and work discipline had a positive and significant effect on the performance of the employees of the regional drinking water company in the City of Parepare by 3,272 > 2,010 and the work environment variable. and work discipline, simultaneously have a significant effect on employee performance variables where F count > F table (62.139 > 3.19).